A Photometric Study of the Galactic Cluster NGC 6124 - Pik Sin The (Institute for Research and Community Services (LPPM) ITB, 1965)
Abstract. Magnitudes and colours on the B, V system are determined for stars in the galactic cluster NGC 6124, based on a photoelectric sequence measured by Koelbloed and an extension of this toward faint stars. The distance of the cluster is about 580 pcs. and the age somewhat more than 108 years. Ichtisar. Magnitudo dan warna dalam sistim B. V daripada bintang2 dalam gugus galaktik NGC 6124 telah ditentukan berdasarkan suatu deret photoelektrik jang diukur oleh Koelbloed dan perluasannja kepada bintang-bintang jang lemah tjahanja. Djarak daripada gugus itu telah ditentukan kira2 580 pc. dan usianja kira2 108 tahun lebih sedikit.